Konsep Perlindungan Hukum Peradilan Bagi Anak Korban Kekerasan Dalam Rumah Tangga - Istiana Heriani; Indah Dewi Megasari; Muthia Septarina (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
The purpose of this study is first to find out how to protect legal protection for children who are victims of domestic violence. Second, to find out how the judicial mechanism is for victims of domestic violence. The research method is normative juridical, with a descriptive approach, namely the results obtained from this study are expected to provide an overview of legal protection for children as victims of domestic violence. The results of his research are legal protection for children as victims of domestic violence, namely the protection provided, including: providing legal assistance; confidentiality of the victim's identity; arrest of the offender with preliminary evidence; providing other assistance in the form of health services; rehabilitation efforts. The judicial mechanism for child victims of domestic violence is with the right handling and approach so that this problem can be handled properly, namely directed to the resolution of domestic violence crimes through restorative justice efforts to restore the rights of victims and relationships with the perpetrators.